A criança com sintomas emocionais e seus pais: um olhar vincular psicanalítico no atendimento infantil - Bastos, Marta Borghetti (Universidade do Vale do Rio dos Sinos, 2012)
This dissertation investigates the psychodynamics of children with emotional symptoms and the functioning of their families. The work is presented through two theoretical and clinical articles, consisting in two case studies in each one of the papers. The case studies were taken from the records of the private practice of the researcher as a clinic psychologist and a child and family psychotherapist. The first section presents a study that shows the use of a child as symptom of the whole family. This kind of case can be used as a device for the study and practice of link psychoanalysis, in that is possible to obtain data about the psychodynamics of the intersubjective processes of the subject and his place in the unconscious group. From the link psychoanalysis point of view, the logic complexity of Morin and the third included Nicolescu, the psycho diagnostics assessment may be an example of interventional technique that provides data collection and understanding of cases so complexes, and it favors the establishment of the bond of the patients with the therapist. This activity may also play an intermediary role in choosing the most appropriate treatment modality, and to facilitate the participation of any family that can demonstrate resistance in the acceptance of family therapy. The second section of the dissertation includes an article on psychotherapeutic processes were the demand for link work was treated. The two cases presented in psychotherapy attendance include psychodynamic symptom analysis in children with pathological indicators of family functioning. We sought to understand the psychodynamic characteristics of the two families: the first one accepted the indication of link psychoanalysis, and the second one refused. In general, the work enabled the discussion about the complexity of psychoanalytic study and work required for the different processes of subjectivity present in family settings.
Keywords: Psicanálise de casal e família; Pesquisa documental; Psicoterapia; Psicodiagnóstico; Psychoanalysis of bond configurations; Documentary; Research; Psychotherapy; Psycho diagnosis; ACCNPQ::Ciências Humanas::Psicologia